A perspective of massive open online courses (MOOCs) and public health - Bettiol, Silvana; Psereckis, Rhea; MacIntyre, Kate (Frontiers in Public Health, 2022)
Massive open online courses (MOOCs) have emerged as an innovative educational technology relevant to and affecting higher education, professional development, and lifelong learning. This paper introduces the principles of MOOCs and reviews the development of these platforms over time. We reflect upon the considerable investment by institutions to develop, deliver and promote such courses, particularly in public health. While open to interpretation, the inherent power, influence, and effectiveness of MOOCs is unquestionable. The potential contribution of MOOCs to public health education is immense, with almost universal reach and access. However, apart from research into participant engagement and knowledge, MOOC-related research and evaluation continue to lag with the rapid proliferation of these courses in response to emerging challenges, as seen with the Coronavirus Disease 19 (COVID-19) pandemic. This makes analyzing the contribution of MOOCs to public health education, health promotion and community programs challenging. This perspective article provides a robust rationale for the necessity of MOOCs and their utility in upskilling health professionals and the general public. It builds on current knowledge to comprehensively explore the factors influencing the development, and application of MOOCs.